Sleep problems in university students – an intervention - Schlarb AA (Dove Medical Press, 2017)
Angelika Anita Schlarb,* Anja Friedrich,* Merle Claßen Faculty of Psychology and Sports, Bielefeld University, Bielefeld, Germany *These authors contributed equally to this work Introduction: Up to 60% of all college students suffer from a poor sleep quality, and 7.7% meet all criteria of an insomnia disorder. Sleep problems have a great impact on the students’ daily life, for example, the grade point average. Due to irregular daytime routines, chronotype changes, side jobs and exam periods, they need specialized treatments for improving sleep. “Studieren wie im Schlaf” (SWIS; (studying in your sleep)) is a multicomponent sleep training that combines Cognitive Behavioral Therapy for Insomnia and Hypnotherapy for Insomnia to improve students’ sleep, insomnia symptoms and nightmares. The aim of the present study is to evaluate the acceptance, feasibility and the first effects of SWIS. Methods: Twenty-seven students (mean =24.24, standard deviation =3.57) participated in a study of pre–post design. The acceptance and feasibility were measured with questionnaires. In addition, the Pittsburgh Sleep Quality Index (PSQI), sleep logs and actigraphy were implemented. Further variables encompassed daytime sleepiness, sleep-related personality traits and cognitions about sleep. Results: Seventy-four percent of the participants reported symptoms of an insomnia disorder, and 51.9% fulfilled all criteria of an insomnia disorder according to the Diagnostic and Statistical Manual of Mental Disorders (fifth edition). Correspondingly, the students suffered from clinically relevant sleep problems according to the PSQI. The SWIS sleep training is a well-accepted and feasible program. Significant improvements were observed in the subjective sleep quality and sleep-related personality traits, as well as clinical improvements in objective sleep measures. Discussion: Findings showed that SWIS is a feasible program for the treatment of sleep problems in college and university students due to its various effects on sleep and cognitive outcomes. Further evaluation of follow-up measurements and additional variables, that is, cognitive performance and mental health, is needed. Keywords: sleep quality, insomnia, nightmares, college students, CBT-I, HT-I